2022
DOI: 10.3389/fimmu.2022.966291
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single-cell transcriptome analysis of the tumor ecosystems underlying cervical cancer metastasis

Abstract: Cervical cancer (CC) is one of the most frequent female malignancies worldwide. However, the molecular mechanism of lymph node metastasis in CC remains unclear. In this study, we investigated the transcriptome profile of 51,507 single cells from primary tumors, positive lymph nodes (P-LN), and negative lymph nodes (N-LN) using single-cell sequencing. Validation experiments were performed using bulk transcriptomic datasets and immunohistochemical assays. Our results indicated that epithelial cells in metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Usually not found in healthy CESC tissue, these cells increase in number in the CESC environment, encircling cancer cells and hindering the activity of effector T cells, ultimately aiding in the evasion of the immune system by the tumor 33 . Our research found that increased levels of Treg cells are linked to a worse outcome in CESC patients with high AGPAT3 expression.Conversely, in patients with low AGPAT3 expression, Treg cell levels did not signi cantly impact CESC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Usually not found in healthy CESC tissue, these cells increase in number in the CESC environment, encircling cancer cells and hindering the activity of effector T cells, ultimately aiding in the evasion of the immune system by the tumor 33 . Our research found that increased levels of Treg cells are linked to a worse outcome in CESC patients with high AGPAT3 expression.Conversely, in patients with low AGPAT3 expression, Treg cell levels did not signi cantly impact CESC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…CAFs can promote tumor cell mitotic proliferation via PDGFC/PDGFRA/SLUG, achieving metastasis and immune escape by regulating E2F, signal transducer and activator of transcription 5 (STAT5), etc. ( 72 , 73 ). The niche with high MC tumor cells exhibited diverse immune infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…TRMs play a vital role in the immune response against tumors 9 . Previous studies have dissected the cellular heterogeneity and molecular profiles of conventional T cells within the TME of CC 25 27 ; however, the same in-depth characterization of TRMs has not been performed in the CC setting. Thus, in this study, we employed scRNA-seq to investigate the population characteristics of TRMs in CC.…”
Section: Discussionmentioning
confidence: 99%